THE IMPACT OF CREDIT RISK AND DEBT COVERAGE ON PROFITABILITY OF BANKS: A COMPARATIVE STUDY ON INDIAN PUBLIC & PRIVATE SECTOR BANKS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The paper is aimed towards investigating  the effect of credit risk and debt coverage on  profitability of Indian banks. Factors that affect  credit risk and debt coverage have been identified  through extent literature. The t-test and  regression were used to examine the difference  between different sectors of Indian commercial  banks and to study the effect of credit risk and  debt coverage on banks’ profitability. The results  implied that there’s significant difference among  select public and private banks. Also, regression  analysis indicated that the credit risk and debt  coverage indicators was statistically significant  to predict the profitability ratios.
Keywords: Credit risk; debt coverage; bank; profitability,; public and private sector banks